Militarization of Anti-peasant Forest Conservation: The Case of the Amazon Forest Reserve Zone (AFRZ) after the Colombian 2016 Peace Agreement (Forest and Society, 2025)
In 2016, the Colombian government signed a peace agreement with the Fuerzas Armadas Revolucionarias de Colombia (FARC) that included the implementation of a Comprehensive Rural Reform (CRR) with the purpose to allocate and formalize land for peasant populations. In parallel, Colombia was committed to implement the global environmental agendas, including efforts to mitigate greenhouse gas emissions (GHG) by reducing deforestation in the Amazon. Campesino communities in Colombia have historically been marginalized and pushed into forested lands and protected areas. This study seeks to understand the configuration of land-use conflicts in the Amazon Forest Reserve Zone (AFRZ) - a land management category in the Colombian Amazon - amid the implementation of the global environmental agendas and the Peace Agreement, with a focus on the environmental justice implications for peasant communities. After undertaking a historical review of peasant colonization of the Amazon, we focus on the administration of the former president Iván Duque (2018-2022) in which military operations were deployed to counteract the increase of deforestation. These operations resulted in the destruction of private and community infrastructure, and the stigmatization, criminalization, and even homicide of rural inhabitants. Militarization is only the most obvious of the conservation strategies that limit access to nature by peasants, who depend on it for their livelihoods. We further explore the environmental justice implications of this military conservation approach through a case study in the village El Camuya, located in San Vicente del Caguán (Caquetá), in the Colombia’s “arc of deforestation”. Using qualitative methods, we demonstrate how the Comprehensive Rural Reform included in the Peace Agreement has been insufficient to fulfill the needs of Amazonian peasants and that, when intersecting with the environmental agendas, it has fostered land use conflicts that can be understood as environmental injustices.
Keywords: Amazon rainforest; Peasants; Deforestation; Militarization of conservation; Environmental justice